Praca z uczniem przejawiającym trudności szkolne. Autorefleksja nauczyciela praktyka - Kadłubowska, Sandra (Rocznik Pedagogiczny, 2019)
The article shows the benefits of educational projects at the stage of early school education: „I work with ozobots – I program perfectly”. The aim of the course was to introduce programming elements into classes using ozobots – educational robots. Research was carried out in order to help the stu- dents overcome developmental difficulties. The evaluation of the project proves that the additional activities that were carried out enhanced the motivation to learn, fostered children’s curiosity, im- proved the self-esteem of students with educational difficulties and, as a consequence, reduced the risk of anxiety disorders and child phobia at the stage of early school education.